-27 + (x + 3) = 2(x + 1) - [7 + (-8 - 3)]
=> -27 + x + 3 = 2(x + 1) - [7 + (-11)]
=> -27 + 3 + x = 2x + 2 - (-4)
=> -24 + x = 2x + 6
=> -24 - 6 = 2x - x
=> -30 = x
=> x = -30
Vậy x = -30
-27 + (x+3) = 2(x+1) - [ 7 + (-8 - 3)]
\(-27+x+3=\) \(2x+2\times1-\left[7-8-3\right]\)
\(-27+3+x=2x+2-\left(-4\right)\)
\(-24+x=2x+2+4\)
\(-24+x=2x+6\)
\(-24-6=2x-x\)
\(-30=x\)
\(\Rightarrow x=-30\)
Vậy \(x=-30\)
-27 + (x+3) = 2(x+1) - [ 7 + (-8 - 3)]
−27+x+3=−27+x+3= 2x+2×1−[7−8−3]2x+2×1−[7−8−3]
−27+3+x=2x+2−(−4)
−24+x=2x+2+4
−24+x=2x+6
−24−6=2x−x
−30=x
x=-30
-27 + [x+3] = 2 [x+1] -[ 7 +[ -8- 3]]
-27 +[x+3]=2[x+1] -[7+-11]
-27+[x+3] =2[x+1]--4
-27 +[x+3]=2[x+1]+4
x+3=2[x+1]+4+27
x+3=2 [x+1]+31
x+3-2[x+1]=31
x+3-[2x+2]=31
x+3-2x-2=31
-x+1=31
-x=31-1
-x=30
SUY RA X= -3O
THE THOI!!!!